Perancangan Media Pembelajaran Teknik Dasar Bola Voli Mengunakan Teknologi Augmented Reality Berbasis Android - Syaiful Ahdan (Inovasi Pembangunan : Jurnal Kelitbangan, 2020)
Learning media is a tool for the teaching and learning process. Volleyball is one of the most accomplished sports in Indonesia. Mastery of basic techniques is important in creating optimal performance in every sport.The basic technique of volleyball is an element that can determine whether you win or lose a match in addition to physical, tactical, and mental conditions.The limited space and time is one of the main factors for a learner in mastering the basic techniques of volleyball, resulting in difficult technique mastery. The contribution to this research is to design learning media for basic volleyball techniques, which users can use to understand the basic techniques of volleyball and provide alternative media for the general public, namely a learning media for basic volleyball techniques using Android-based augmented reality technology. The system is built using Unity software that works on the Android platform, the system development method used is the MDLC (Multimedia Development Life Cycle) method. The system was tested using ISO 9126 with a Usability value of 89%, 98% Functionality, and 73% Portability. Based on the results of several tests that have been carried out, it shows that the application of learning media can be used by the general public as a learning medium to increase knowledge about volleyball, especially the basic techniques of volleyball.